Update on Pediatric Sepsis in Mexico - Crisell Arely Donath Benitez; Estefanía Mattenberger-Cantú; Ricardo Salas-Flores; Guillermo Baudelio Gómez-Morales; Paola Alejandra Mártinez-Diaz; María Guadalupe Moreno-Treviño; Laura Elvira García-Tovar; Francisco González-Salazar (SAGE Publishing, 2022)
The main objective of this work was to determine and update the causal agents' antibiotic sensitivity and resistance patterns on pediatric sepsis in a population of northeast Mexico. It is a cross-sectional study showing the results of blood cultures of pediatric patients with a presumptive diagnosis of sepsis were reviewed according to the SOFA criteria during 2020 in a public hospital in Mexico. A total of 207 blood cultures were performed and analyzed. The main isolated microorganisms were Staphylococcus, followed by Klebsiella and Escherichia. Several microorganisms showed 100% of sensitivity to different antibiotics or antifungals, some of them include Vancomycin, Voriconazole, Meropenem, Ciprofloxacin, and Cefotaxime. Bacteria of genre Staphylococcus showed its highest sensitivity rate to Tigecycline with 63.3%. Too Staphylococcus showed the highest resistance rate to Oxacillin with 50%. Although the patterns of sepsis-causing germs are similar to those previously reported, the development of new drugs with greater efficacy is the main contribution.